2019 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--32290
|View full text |Cite
|
Sign up to set email alerts
|

Board 19: The Impact of a Research Experiences for Teachers Program in Precision Agriculture and Sustainability for Rural STEM Educators

Abstract: program. He has a B.S. in Civil Engineering from Virginia Tech and a Master's of Civil Engineering and an Ed.D. in Technology Education both from N.C. State University. Using his work experience in both engineering and education, he specializes in designing integrative STEM activities for K-12 students and implementing professional development programs for K-12 educators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 5 publications
2
9
0
Order By: Relevance
“…They expressed an increased commitment to granting students more responsibility for navigating their way through the process and providing additional time to struggle with the iterative nature of designing. This outcome supports existing research reporting that teachers are significantly more motivated to integrate the EDP into their classroom practices after participating in an authentic engineering-focused RET program (Bowen et al, , 2019(Bowen et al, , 2021DeJong et al, 2016;Yelamarthi et al, 2013). Teachers in this study also expressed ownership and buy-in for implementing the EDP due to increased familiarity with the nature of the EDP and readiness to translate it from an engineering research setting into a classroom setting.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…They expressed an increased commitment to granting students more responsibility for navigating their way through the process and providing additional time to struggle with the iterative nature of designing. This outcome supports existing research reporting that teachers are significantly more motivated to integrate the EDP into their classroom practices after participating in an authentic engineering-focused RET program (Bowen et al, , 2019(Bowen et al, , 2021DeJong et al, 2016;Yelamarthi et al, 2013). Teachers in this study also expressed ownership and buy-in for implementing the EDP due to increased familiarity with the nature of the EDP and readiness to translate it from an engineering research setting into a classroom setting.…”
Section: Discussionsupporting
confidence: 83%
“…Integrating engineering or scientific research into teacher professional development has shown to increase teachers' awareness of the need to incorporate authentic learning activities into their classroom practices regularly (Barrett et al, 2015;Barrett & Usselman, 2005Basalari et al, 2017;Bowen et al, , 2019Bowen et al, , 2021Farrell, 1992;Kantrov, 2014;Silverstein et al, 2002Silverstein et al, , 2009. Teachers have reported a shift in their pedagogical approach to incorporate the use of more workforce skills in the classroom as a result of participating in targeted professional development (Bowen & Shume, 2018Darling-Hammond & Baratz-Snowden, 2005;Stewart, 2014;Webb, 2015).…”
Section: Professional Development In Stem Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although RETs that focused more pointedly on teacher practice was more successful in shaping teachers' beliefs and practices, teachers still need to have explicit help in translating scientific inquiry into their teaching knowledge and practice (Roseler, et al, 2012). In addition, RET programs improve teachers' functionality as scientists (Faber et al, 2014), increase their understanding of design-based learning, workforce skills (i.e., 21st century skills), and the engineering design process skills (Bowen et al, 2021), improve teachers' confidence and growth in their understanding of STEM curriculum (Schneider et al, 2020) and their inquiry conceptions and lesson design (Blanchard & Sampson, 2018), and increase STEM awareness teaching practices potentially contribute to preparing more students for STEM careers (Pinnell et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Before this review paper discusses the above topic of concern in Section 5 , the basic understanding of the agroecosystem [ 165 , 166 , 167 , 168 ], I4 for PA [ 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 ...…”
Section: Introductionmentioning
confidence: 99%